Forms of carbon in an oxisol under no-tillage and crop-livestock integration systems in the cerrado, Goias State, Brazil - Bezerra, Régis Pinheiro Martins; Loss, Arcângelo; Pereira, Marcos Gervasio; Perin, Adriano (Semina: Ciências Agrárias, 2013)
The no-tillage system (NTS) and more recently, the crop-livestock integration (CLI) are very used for grain production in the Cerrado biome. This, the soil organic matter (SOM) is one of the main components responsible for maintaining the quality of tropical soils. This study aimed to quantify the levels of total organic carbon (TOC), total nitrogen (total N), water soluble carbon (WSC) and carbon of humic fractions in areas with different land use systems in the Cerrado of Goias. The farming systems were used: CLI (brachiaria + corn/beans/cotton/soybean) and NTS (sunflower/millet/soybean/corn) andas a reference, area native Cerrado vegetation (Cerradão). We collected soil samples at 0-10, 10- 20, 20-30 and 30-40 cm. The contents of TOC, total N, WSC, humin fraction carbon (C-HUM), humic acid fraction (C-HAF) and fulvic acid fraction (C-FAF). The area of Cerradão had the highest TOC, total N, C-HUM and C-FAH in the surface layer (0-10 cm). The levels of WSC and humic fractions of SOM showed significant differences between the systems of land use and sampling depths. The highest levels of C-HAF were found in the area of CLI, at 0-10 and 20-30 cm. The CLI systems and NTS did not differ for the TOC and total N except for N in layer 20-30 cm. The system CLI favors the formation of C-HUM compared to the NTS. The CLI system leads to lower levels of WSC and higher C-FAF compared with the NTS, which has higher levels of WSC and C-FAH. The use of WSC and carbon of humic fractions was more efficient to identify differences from the land use systems evaluated (NTS, CLI and Cerradão) when compared to the TOC for the climatic conditions of this study.